PROBIOTIC SUPPLEMENTATION IN INFANTILE COLIC: A COMPARATIVE LITERATURE REVIEW BETWEEN BREASTFED AND FORMULA-FED INFANTS - Sais, Vira Cendana; Putri, Erika Aini; Yustisiani, Aliffa Neta; Falakhi, Qoniatunnisa Nuzulul; Penadi, Hafidhania; Amalia, Nurlinah (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2026)
Background: Infantile colic is a functional gastrointestinal disorder in infants under five months, marked by excessive, unexplained crying, and is increasingly linked to gut dysbiosis and intestinal inflammation. Probiotics may help relieve colic by modulating gut microbiota, with effects differing by feeding type. Objective: This study aims to evaluate the effectiveness of probiotics in managing infantile colic, with a focus on differences in outcomes between exclusively breastfed and formula-fed infants. Methods: This literature review identifies randomized controlled trials and cohort studies involving infants aged 0–12 months that are diagnosed with colic and receiving probiotics. The outcomes are crying frequency and duration, or symptom improvement, and compared effects between exclusively breastfed and formula-fed infants. Seven databases were searched using combinations of relevant keywords, limited to publications from the past five years. Data were synthesized using narrative qualitative analysis. Results: From 1,886 initially identified records, 29 studies met the eligibility criteria after screening and full-text assessment. Among the included studies, 13 investigated probiotics alone, 10 focused on breastfed infants, 4 on formula-fed infants, and 2 involved both feeding types. Most studies supported the efficacy of Lactobacillus reuteri DSM 17938 in reducing crying duration and frequency, particularly in breastfed infants. Formula-fed infants showed variable outcomes, potentially influenced by probiotic strain, feeding composition, and study design. Conclusion: Probiotics, especially Lactobacillus reuteri, demonstrate promising effects in alleviating colic symptoms, predominantly among breastfed infants. Feeding type may act as a modifier of probiotic efficacy, highlighting the need for tailored interventions based on nutritional context.